Insulin-like growth factor I, IGF binding protein 3, and IGFBP protease activity: relation to anthropometric indices in solid tumours or leukaemia. Issue 3 (1st March 1999) - Brennan, B M D; Gill, M; Pennells, L; Eden, O B; Thomas, A G; Clayton, P E
Abstract : OBJECTIVES: To measure the serum concentrations of insulin-like growth factor I (IGF-I) and IGF binding protein 3 (IGFBP-3), and the level of IGFBP-3 protease activity in 38 children presenting with malignancies, and to assess their relation with auxological parameters and nutritional status. METHODS: Height, weight, skinfold thickness, and mid-upper arm circumference (MUAC) were recorded using standard techniques. IGF-I and IGFBP-3 were measured using specific radioimmunoassays. Serum IGFBPs were also visualised on western ligand blot. IGFBP-3 protease activity was assessed by the extent of fragmentation of recombinant [ 125 I]-IGFBP-3, compared with that induced by pregnancy serum. Anthropometric and radioimmunoassay data were expressed as standard deviation scores (SDS). RESULTS: The median (range) IGF-I SDS was significantly reduced in all patients (−1.1 (−5.1 to 1.2)) and lower in children who were malnourished (−2.5 (−3.9 to 0.1)). IGFBP-3 SDS was within the normal range for 31 of 38 patients but IGFBP-3 protease activity was raised in all patients. Neither IGFBP-3 concentration nor protease activity was affected by nutritional status. IGF-I correlated with MUAC ( r  = 0.41) and subscapular skinfold thickness SDS ( r  = 0.38), but not with weight, height, weight for height, or triceps skinfold thickness. CONCLUSIONS: IGF-I is low in children with malignancies, and even lower in those who are malnourished. IGFBP-3 concentrations were normal in most patients but interpretation is complicated by the presence of raised IGFBP-3 protease activity, which could lead to overestimating concentrations of intact peptide. IGF-I appears to relate to arm anthropometry as an index of nutritional status but not height, weight, or weight for height, as would be expected in normal children.